Aggregate breakdown and dispersion of soil samples amended with sugarcane vinasse - Ribeiro, Bruno Teixeira (2013)
Soil aggregation is a very complex issue related to important soil attributes and processes. The aggregate breakdown and dispersion of soil samples amended with sugarcane vinasse were evaluated using ultrasonic energy. Vinasse is an important byproduct of sugarcane industries, intensively applied to soils in Brazil as liquid fertilizer. Samples of two Oxisols and one Ultisol were used in this study. The physical and chemical characterization of soils was performed, and the 1 to 2 mm size aggregates (200 g) were packed in PVC columns (6.0 cm high and 4.0 cm internal diameter) and incubated with sugarcane vinasse under lab conditions for 1, 30 and 60 days. After incubation, aggregates were submitted to levels of ultrasonic energy, and the particle size distribution (53 to 2,000 µm, 2 to 53 µm, and < 2 µm fractions) was quantified. Mathematical equations were used to relate the mass of aggregates in each of these fractions to the applied ultrasonic energy, and parameters related to aggregate stability were then obtained. Soils showed an aggregate-hierarchy resulting in a stepwise breakdown under ultrasonic agitation. Considering this soil-aggregation hierarchy, vinasse contributed even in a short time to the bonding between and within 2 to 53 µm aggregates, mainly in the Oxisols. This may be related to organic compounds present in the vinasse, cementing soil particles. Potassium enrichment of soil samples did not contribute to soil dispersion.